Emergence of size induced metallic state in the ferromagnetic insulating Pr0.8Sr0.2MnO3 manganite: Breaking of surface polarons - DAS, PROLOY TARAN; Nigam, Arun Kumar; Nath, Tapan Kumar (JOURNAL OF ADVANCES IN PHYSICS, 2015)
Nano-dimensional effects on electronic-, magneto-transport properties of granular ferromagnetic insulating (FMI) Pr0.8Sr0.2MnO3 (PSMO) manganite (down to 40 nm) have been investigated in details. From the electronic and magnetic transport properties, a metallic state has been observed in grain size modulation by suppressing the ferromagnetic insulating state of PSMO bulk system. A distinct metal-insulator transition (MIT) temperature around 150 K has been observed in all nanometric samples. The observed insulator to metallic transition with size reduction can be explained with surface polaron breaking model, originates due to enhanced grain surface disorder. This proposed phenomenological polaronic model plays a significant role to understand the polaronic destabilization process on the grain surface regime of these phase separated nano-mangnatie systems. Temperature dependent resistivity and magnetoresistance data in presence of external magnetic fields are investigated in details with various compatible models.